2011
DOI: 10.31018/jans.v3i1.154
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of nursery bed inoculated arbuscular mycorrhiza and rootdip inoculated Azotobacter chroococcum and Aspergillus awamori on aerobic rice

Abstract: Field evaluation of nursery bed inoculated with Glomus fasciculatum and root dip treatement with Azotobacter chroococcum and Aspergillus awamori was carried out on aerobic rice. All the inoculated treatments with G. fasciculatum either singly or incombination showed increased growth and yield of rice compared to control and dual and triple inoculation were performed better than single inoculation treatment. G. fasciculatum inoculated seedlings in nursery bed shown better root colonization in field after transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Recent advances have shown that microbial consortia containing mycorrhizal inoculant are effective [130,131]. Microbial consortia showed increased growth and yield of rice compared to the control [132,133]. The interaction effect of consortium of Azospirillum, PSB, and AMF fungus could reduce levels of N and P fertilizers in the growth of directly seeded rice [134].…”
Section: Potential Application Of Amf Mutualism In Paddy Fieldsmentioning
confidence: 99%
“…Recent advances have shown that microbial consortia containing mycorrhizal inoculant are effective [130,131]. Microbial consortia showed increased growth and yield of rice compared to the control [132,133]. The interaction effect of consortium of Azospirillum, PSB, and AMF fungus could reduce levels of N and P fertilizers in the growth of directly seeded rice [134].…”
Section: Potential Application Of Amf Mutualism In Paddy Fieldsmentioning
confidence: 99%
“…By increasing the nutrient status and quality of the soil, these advantageous microorganisms that form colonies in and around root systems support plant growth. Research has demonstrated the favorable effects of applying microbial consortia made up of particular microorganisms on plant growth, particularly when the microorganisms are inoculated in nursery beds or root trainers during the seedling stage [16,17].…”
Section: Introductionmentioning
confidence: 99%